Peran Guru Pendidikan Pancasila Dan Kewarganegaraan Dalam Membentuk Sikap Dan Kepribadian Peserta Didik - Uswatun Hasanah (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2021)
Along with the times, individual attitudes and personalities have changed, there have been many juvenile delinquencies at school and outside of school. Teachers are educators who become figures, role models, and identification for their students. Teachers also have the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in formal education, basic education, and secondary education. The teacher's direction becomes a guide for the activities of the students. A teacher not only teaches, but also educates and trains students in order to achieve the expected learning goals. This study aims to determine the role of Pancasila and civic education teachers in shaping the attitudes and personalities of students at SMP Negeri 9. This study used a qualitative descriptive research method. The results of this study indicate that the role of teachers in shaping the attitudes and personalities of students is very important. The role of teachers in shaping the attitudes and personalities of students can be by forming students so that they have a love for the country, have a strong sense of nationality, foster mutual respect and respect for fellow humans in school life and in society, always obey the rules apply, and shape students to recognize that Indonesia is a pluralistic country consisting of various religions, races, ethnicities, languages and cultures